2017
DOI: 10.1007/s10311-017-0644-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of protein biomarkers of mercury toxicity in fish

Abstract: Bioaccumulative metals such as mercury are found in increasing amounts in fish and their consumers. In the region of the Madeira River, in the Brazilian Amazon, mercury (Hg) is a predominant contaminant in the aquatic ecosystem. There is therefore a need to find specific biomarkers of mercury toxicity in fish to monitor contaminations. Here, mercury-bound proteins were identified in the liver tissues of fishes Mylossoma duriventre and Brachyplatystoma rousseauxii. Mercury was quantified in liver tissue, pellet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 29 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…For example, it has been shown that multiple Hg-binding proteins (e.g. metallothionein), which is one of the detoxification strategies along with Hg elimination in fish (Pan & Wang, 2012), are less efficient in carnivorous than in herbivorous fish species (Vieira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that multiple Hg-binding proteins (e.g. metallothionein), which is one of the detoxification strategies along with Hg elimination in fish (Pan & Wang, 2012), are less efficient in carnivorous than in herbivorous fish species (Vieira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to use safe and secure fish free of heavy metals. The US Food and Drug Administration (FDA) recommends avoiding predatory fish such as sharks due to their high mercury content [6,9,10].…”
Section: Mercurymentioning
confidence: 99%
“…The chronic intoxication leading to skin defects and cancer [6,7]. Mercury poisoning causes damage to the nervous system, kidney damage, interference with the reproductive system and suppression of the immune system, and exacerbation of lupus [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The species of fish that are most consumed by the population of this region include: dourada (Brachyplatystoma rousseauxii), filhote (Brachyplathystoma filamentosum), tucunaré (Cichla spp. ), tambaqui (Colossoma macropomum), pirarucu (Arapaima gigas), piranha preta (Serrasalmus rhombeus), and barba chata (Pinirampus pirinampu) [4]. Among these species, dourada, filhote, tucunaré, pirarucu, piranha preta, and barba chata feed mainly on smaller fish, while the tambaqui is omnivorous, feeding principally on aquatic plants but also on small fish [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the mercury concentrations in fishes consumed in the Brazilian Amazon region should be constantly monitored. In this context, new methodologies for mercury determination in fish tissue samples will contribute to the control of mercury concentration in fish [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%